Organized and curated by Klitsa Antoniou and the Contemporary Visual Art Practices Lab - Antoniou, Klitsa (My University, 2026)
Collaborative Art Project initiated and organized by Klitsa Antoniou and the Contemporary Visual Art Practices Lab. Artists with international recognition and acclaimed work are invited to share aspects of their work with the students of the Department, as well as the general public. The aim of the annual project is on the one hand to offer students a recording and analysis of the work of the invited artists, and on the other hand to familiarize them with experimental artistic interventions of a collaborative nature by creating together a work of participatory art.